Longitudinal Associations of the Healthy Lifestyle Index Score With Quality of Life in People With Multiple Sclerosis: A Prospective Cohort Study - Leong, Teng I.; Weiland, Tracey J.; Jelinek, George A.; Simpson, Steve; Brown, Chelsea R.; Neate, Sandra L.; Taylor, Keryn L.; O'Kearney, Emily; Milanzi, Elasma; De Livera, Alysha M. (Frontiers in Neurology, 2018)
Objective: To explore the association between combined lifestyle risk factors with quality of life in people with multiple sclerosis (MS) over 2.5 years. Methods: People with MS were recruited to participate in a comprehensive online survey regarding their demographic and clinical characteristics, health-related quality of life (HRQOL) and lifestyle behaviours including physical activity, alcohol consumption, cigarette smoking, body mass index and dietary habits measured at baseline and 2.5-year follow-up. A combined healthy lifestyle index score (HLIS) was constructed by assigning scores of 0-4 to each of the lifestyle risk factors, for which higher values indicate healthier lifestyle behaviour. Multivariable linear regression modelling was used to assess whether the HLIS at baseline was associated with the physical and mental HRQOL over the study period in this sample of people with MS. Results: Of 2466 participants with confirmed MS, 1401 (57%) completed the follow-up. Multivariable linear regression analyses demonstrated that every 5-point increase (of a possible total of 20) in the baseline HLIS was associated with 5.2 (95% Confidence Interval (CI): 3.1-7.2) and 1.7 (95% CI: 0.2-3.2) higher mean scores in the physical HRQOL component at follow-up and the change in physical HRQOL component from baseline to follow-up respectively; and 5.9 (95% Confidence Interval (CI): 4.1-7.7) and 2.5 (95% CI: 1.0-4.0) higher mean scores in the mental HRQOL component at follow-up and the change in mental HRQOL component from baseline to follow-up respectively. Conclusion: Findings suggest the importance of healthy lifestyle behaviour in quality of life in MS. A healthy lifestyle program focusing on these behaviours has the potential to positively influence health-related quality of life for people with MS.